Death in captivity - Gilbert, Michael Francis, 1912-2006 (Poisoned Pen Press, 2019)
"Any book by Michael Gilbert is a treat'--Daily Telegraph. A man is found dead in an escape tunnel beneath an Italian prisoner-of-war camp. Did he die in an accidental collapse--or was this murder? Captain Henry 'Cuckoo' Goyles, master tunneller and amateur detective, takes up the case. This classic locked-room mystery with a closed circle of suspects is woven together with a thrilling story of escape from the camp, as the Second World War nears its endgame and the British prisoners prepare to flee into the Italian countryside"--